2017
DOI: 10.15171/jlms.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Effect of Extremely Low-Frequency Electromagnetic Fields (ELF-EMF) With Different Intensities in SH-SY5Y Neuroblastoma Cell Line

Abstract: Introduction: During the last 3 decades, human is exposed to extremely low frequency electromagnetic fields (ELF-EMF) emitted by power lines and electronic devices. It is now well accepted that ELF-EMF are able to produce a variety of biological effects, although the molecular mechanism is unclear and controversial. Investigation of different intensities effects of 50 Hz ELF-EMF on cell morphology and protein expression is the aim of this study. Methods: SH-SY5Y human neuroblastoma cell line was exposed to 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Rezaire-Taviraini et al, in their work, postulate that EMF with a frequency of 50 Hz affects the morphology of SH-SY5Y cells (neuroblastoma cell line), but without specifying any differences. In their work, researchers try to convince that the differences result from altered gene expression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rezaire-Taviraini et al, in their work, postulate that EMF with a frequency of 50 Hz affects the morphology of SH-SY5Y cells (neuroblastoma cell line), but without specifying any differences. In their work, researchers try to convince that the differences result from altered gene expression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced metastatic properties of tumor lines after EMF exposure are also confirmed by the results of the migration and invasion assays. This may be due to slight changes in the extracellular matrix, and not, as some scientists claim, the influence of EMF on the cytoskeleton of cancer cells [ 10 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions determine the effect in the exposed samples. A proteomic study in SH-SY5Y cells exposed to 0.5 and 1 mT at 50 Hz for 3 h revealed that cell morphology, proliferation rate, and protein expression can be affected in a dose-dependent manner by an increased intensity of ELM-EMF exposure [Rezaie-Tavirani et al, 2017]. In addition, it has been demonstrated that pulsed EMFs can promote either proliferation or cell death, in an amplitude-, frequency-, and exposure-time-dependent manner [Akbarnejad et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…4 Additional information in this relationship could be achieved via the bioinformatic study of molecular data such as proteomics. 12 Moreover, bioinformatics is a useful method to study mechanism of laser therapy via analyzing the most central biomarkers in an interaction network. 8 Here, the proteomics data of IR laser treatment on myoblast (C2C12 cell line) of Murine 4 were employed for our bioinformatic assessments.…”
Section: Introductionmentioning
confidence: 99%